(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the thematic complexity and narrative structure of Wizarding World created by J. K. Rowling in the Harry Potter series. The study explores how the fictional universe combines mythological patterns, social commentary, and moral philosophy within a coherent literary structure. Using qualitative textual analysis and comparative literary methods, the article investigates the representation of identity, friendship, power, morality, discrimination, and heroism across the series. Particular attention is devoted to the structural organization of novels, including the hero’s journey, episodic progression, symbolic spaces, and the interaction between magical and non-magical societies. The findings demonstrate that Rowling’s Wizarding World functions not merely as an imaginative fantasy setting but also as a reflection of modern social, political, and ethical concerns. The article concludes that the enduring cultural significance of the Harry Potter universe lies in its successful integration of universal themes with a sophisticated narrative structure that appeals to diverse generations of readers.